IMPELEMENTASI KEBIJAKAN PEMERINTAH DAERAH KAB. GORONTALO UTARA TERHADAP WISATA BUDAYA RITUAL MANDI SAFAR - Febrianto Hakeu; Sri Sunarti (Tulisan Ilmiah Pariwisata (TULIP), 2019)
AbstractThis article aims to determine the Shafar Bathing Ritual Process in Kec. Atinggola Buata Village, North Gorontalo Regency, and knowing the Implementation of Regional Government Policies in the Cultural Tourism sector towards Shafar Bathing Rituals in North Gorontalo District, and formulating solutions to the identified constraints. This article is analyzed based on a descriptive qualitative approach. The results of the analysis of this article are 1) Shafar's bathing ritual starts from the morning at 06.30 WIB with the recitation of Al-Quran verses (Surah Al-Kahfi, Surah Yasin), and the traditional event of bathing Shafar then ends with eating together. 2) Tourism development in Atinggola District is quite good, seen from the policy of the District Government. North Gorontalo and 3) In implementing tourism development, the Tourism and Culture Office always tries to develop tourism in Atinggola District, namely by carrying out tourism promotion programs, tourism destination development programs, and tourism partnership programs. The tourism promotion program is carried out by organizing the Shafar bathing ritual which is carried out once a year in addition to tourism promotion via the internet. While the tourism partnership program, the Tourism and Culture Office collaborates with several related agencies to help develop tourism in Atinggola District.